Pengaruh Current Ratio (CR) dan Net Profit Margin (NPM) Terhadap Harga Saham pada Perusahaan Makanan & Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Rahmawati, Nopiyanti; Maulana, Rizal; Alfiana, Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of the Current Ratio and Net Profit Margin on stock prices using a panel data regression approach. The data used in this study are secondary data in the form of corporate financial statements and stock prices over a specific observation period. The analytical method employed is panel data regression with the Random Effect model, which was selected based on the results of the model selection tests. The results indicate that, partially, the Current Ratio has no effect on stock prices, while the Net Profit Margin has an effect on stock prices. Simultaneously, the Current Ratio and Net Profit Margin jointly influence stock prices. The findings also show that the Current Ratio and Net Profit Margin variables are able to explain 48.99% of the variation in stock prices, while the remaining 51.01% is influenced by other factors outside the variables examined. Therefore, this study is expected to serve as a reference for investors and company management in making investment decisions and evaluating corporate financial performance in the future.